Barriers to telework expansion in the COVID-19 pandemic (Research, Society and Development, 2021)
The COVID-19 pandemic, the oil crisis of 1973 and 1979, and unemployment in Europe in the 1980s have in common the breaking of paradigms and behavioral changes that have required changes in labor relations. The advance of technology has enabled the application of telework as an alternative to reduce congestion and pollution. However, there were perceived advantages in improving the quality of life and reducing costs, but behavioral changes were required, so that isolation, self-employment, and a sense of responsibility demanded new skills in its application. A survey was carried out to compare the result with the sociotechnical system in an engineering company. There was a consensus to reduce by one or two days a week, in addition to delegating more responsibility to employees, there was an acceptance of increased workload to compensate for freedom of choice.